Determinan Pengungkapan Islamic Social Reporting ( Studi Empiris Pada Perusahaan yang Masuk dalam Daftar Efek Syariah Tahun 2013-2015) - Miskiyah, Arikhotul, Drs.M.Abdul Aris,M.Si (2016)
Islamic Social Reporting (ISR) is an index of responcibility disclousurethat a specific indicator on the ethical principles of Islam. The purpose of the reseach is to examine whether the company size, profitability, environmental performance and boart size is a determinant Islamic Social Reporting on companies included in the list of Islamic securities. Determinant used include company size, profitability, environmental performance and board size. Population used in this reseach are all companies included in the list of Islamic securities the period 2013-2015. The sampling method by mean purposing sampling with a total sample of 102 companies. Analysis method of data used in this research is multiple linear regression. The result showed that environmental performance is determinant disclosure of Islamic Social Reporting. While the company size, profitability, performance and board size is not a determinant of Islamic Social Reporting.